Revitalization of Customary Law as a Source of Law in Building a Legal System in Indonesia - Saly, Jeane Neltje; Cahyadi, Silvia; Joshua, Mishael; Immanuel S, Maurend Benaya (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
In this research, data and information will be collected in an interdisciplinary and multidisciplinary manner and involve different sectors. The collected data and information will be analyzed in an in-depth normative juridical way to obtain a comprehensive understanding of customary law. This shows that customary law has important values and contributions to the development of national law, even in the era of globalization and technological developments that are constantly changing. This research examines which areas of customary law are still relevant in overcoming the problems faced by the Indonesian nation in the era of globalization, and how is the revitalization of customary law as a source of law in building the legal system in Indonesia.